أثر الانفاق الحكومي على النمو الاقتصادي في سورية دراسة قياسية للفترة (1990 – 2010) - ديوب محمد (Latakia University Journal - Economic and Legal Sciences Series, 2018)
لقد أدى السؤال المطروح فيما إذا كان الإنفاق الحكومي يحفز النمو الاقتصادي إلى تقسيم صانعي السياسة إلى معسكرين نظريين، فالبعض يؤيد تدخل الدول بشكل كبير والبعض الآخر يؤيد تدخلها بشكل محدود، ومن جهة أخرى فإن النظرية الاقتصادية تشير إلى أنه وفي بعض الحالات يكون الإنفاق العام عند مستويات منخفضة محفزا للنمو الاقتصادي وفي حالات أخرى يتطلب تحفيز النمو الاقتصادي إنفاقا حكوميا أعلى، وإذا ما أخذت الدراسات التجريبية بعين الاعتبار فإن الأمر يصبح أكثر تعقيدا، وذلك وفقا للمنهج الذي تفضله هذه الدراسات. تتحقق الدراسة من أثر الإنفاق الحكومي على النمو الاقتصادي السوري، باستخدام سلاسل زمنية سنوية ل 21 سنة للفترة بين (1990- 2010)، بتطبيق منهج الانحدار الذاتي للفجوات الزمنية الموزعة المتباطئة، حيث تم إدخال الناتج المحلي الإجمالي الحقيقي كمتغير تابع، والإنفاق الحكومي الجاري والرأسمالي كمتغيرين مستقلين تؤكد النتائج وجود أثر إيجابي ومعنوي للإنفاق العام الجاري على الناتج المحلي الإجمالي، وهذا ما يدعم الفرضية الكينزية، في حين أن الإنفاق الحكومي الرأسمالي، ليس له أثر معنوي على الناتج المحلي الإجمالي، وهذا ما قد يفسره انخفاض حجم الإنفاق الحكومي الرأسمالي عن المستوى الذي يضمن تحفيز معدل نمو الناتج المحلي الإجمالي. The question whether or not government expansion causes economic growth has divided policy makers into two distinctive theoretical camps, as proponents of either big government or small government. Economic theory would suggest that on some occasions lower levels of public expenditure would enhance economic growth while on other occasions higher levels of public expenditure would be more desirable. From an empirical perspective the evidence generated becomes more confusing as a number of studies favour one or the other approach. Using time series data of 21 years period (1990 -2010), this study investigated the impact of government spending on the Syrian economic growth. Employing Autoregressive Distributed Lag (ARDL) method to estimate the model specified. Real Gross Domestic Product (RGDP) was adopted as the dependent variable while government capital expenditure (GCEXP) and government recurrent expenditure (GREXP) represents the independent variables. the results confirm a positive and statistically significant relationship between the government recurrent expenditure and the Real Gross Domestic Product, which supports Keynesian Hypothesis. The government capital expenditure has insignificant relationship with the Real Gross Domestic Product in the short and long run. The explanation for this finding could be that the level of capital expenditure is too small in Syria over the period (1990- 2010), not being sufficient enough to alter the GDP growth rate.